Republic of Croatia : 2009 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Croatia. (IMF Staff Country Reports; Country Report, 2009)
Croatia's annual GDP growth accelerated to 4-5 percent, per capita incomes advanced further toward the EU average, and unemployment declined to the lowest levels since Croatia's independence. The staff report for Croatia's 2009 Article IV Consultation is also described. Rapid credit growth led to a significant debt build-up and prevalent foreign currency borrowing aggravated balance sheet vulnerabilities, and booming domestic demand led to surging trade deficits, moderated only partially by strong tourism earnings.